Development of a rapid and efficient analytical method for trace lead determination: Manganese dioxide nanoflower based dispersive solid-phase extraction. (April 2023) - Öner, Miray; Demir, Cansu; Çetin, Gülten; Bakırdere, Sezgin
Graphical abstract: Lead (Pb) is a heavy metal that is highly toxic and a major environmental pollutant. Anthropogenic activities are the main sources of Pb release into the air, water and food, from which humans and other organisms become exposed. In this study, a suitable, rapid, and environmental friendly dispersive solid phase extraction procedure based on manganese dioxide nanoflower (MnO2 NF-DSPE) was developed for the effective enrichment of Pb coupled with flame atomic absorption spectrometry (FAAS). Under the optimal experimental conditions, limit of detection (LOD), quantification (LOQ) values and enhancement in detection power (EDP) obtained for the MnO2 NFs-DSPE-FAAS system were calculated as 6.1 µg/L, 20.3 µg/L and 44, respectively. Three different ginger tea samples were used in recovery studies to investigate the applicability/accuracy of the proposed method. Matrix matching calibration strategy was performed in recovery studies and percentage recoveries were calculated between 106 and 122% with low standard deviation values. Highlights: Trace level lead was preconcentrated by DSPE prior to FAAS measurement. MnO2 nanoflowers were used as adsorbent in the extraction procedure. LOD and LOQ for ginger tea matrix were 6.09 µg/L and 20.29 µg/L, respectively. The detection limit for conventional FAAS system was improved by about 43.7 folds. Recovery results for the prepared ginger tea were found in the range of 106.1–121.5%.